Early Gastric Cancer - Gontar A. Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Early Gastric Cancer (EGC) is a carcinoma limited to the gastric mucosa or submucosa without the involvement of any lymph node. In Indonesia, the prevalence of EGC in 1980 was 2.2% and 1.7% for Jakarta and Medan, respectively. From 1980-1987 in Surabaya, the prevalence was 9.1% from all gastric cancers. Gastric mucosal abnormalities include atrophic gastritis, which is frequently accompanied by achlorhidria or hipochlorhidria and pernicious anemia, and the presence of an ulcer or polyp were believed to be precarcinogenic factors. Environmental factors, life style, age, sex, genetic factors, race, as well as dietary factors, especially intake of foods containing N-nitrosa (N-nitrosa compound) might play a role as risk factors for EGC. H.pylori infection also causes an increased risk for EGC. The diagnosis of EGC is based on physical examination, occult blood in stool sample, cytology, double contrast roentgenologic examination, gastroscopy, gastrobiopsy, and radioactive phosphor. There are no tumor markers specific for EGC. Histologically, EGC is classified into intestinal and diffuse infiltrative EGC. In 1962, the Japanese Research Society for Gastric Cancer made a classification for EGC based on  gastroscopy, fluoroscopy, histopathology and microscopic examinations. In Japan, detection for EGC was performed by spraying the gastric mucosa with methylen blue during endoscopy, which will stain intestinal mucosa and spare normal mucosa. Early detection of EGC in Japan was performed through mass screening of people ages 40-50 years with recent dyspepsia, by means of endoscopy, biopsy, and upper GI tract radiological examinations. Endoscopic Ultrasonography (EUS) is the most accurate tool to determine EGC staging, particularly those with non-ulcerative lessions. The choices of treatment for EGC are surgical therapy or Endoscopic Mucosal Resection (EMR). EMR is a localized therapy, and it is indicated for EGC without metastases, for patients unwilling to undergo operation, or for those who are bad candidates for operation. The prognosis for EGC does not depend upon microscopic classification, but mostly on the depth of gastric mucosal invasion, spread to regional lymph nodes, and the presence of distant metastases. By establishing the diagnosis of EGC, the prognosis is usually better, for the treatment can be given at an earlier stage.   Key words: Early gastric cancer, diagnosis, treatment